New options in the treatment of autosomal dominant polycystic kidney disease. (16th February 2015) - Kazancioglu, Rumeyza; Gursu, Meltem
Abstract: Autosomal dominant polycystic disease (ADPKD) is one of the most common monogenic disorders, and globally is among the most common hereditary causes of end stage kidney disease. Until recently, the causes of this disease remained obscure. However, in the past decade there have been enormous advances in the understanding of the pathophysiology and genetics of this condition, and recent studies have suggested the possibility of specific treatment for slowing cyst growth. This review will focus on the new options for the control of ADPKD.